GUI abstraction of a sensor field on mobile device - Chauhan, Gaurav (Kansas State University, 2010)
A sensor network can be used to observe events performed by physical entities and their physical locations. The growing need of wireless sensor networks to monitor different events can be accomplished by tiny computing platforms called Motes. Having a GUI abstraction of the region can help in getting a heads up display of the region which can be used for several purposes, e.g. in hospitals for tracking different events in case of a fire emergency. It can be helpful for firefighters entering a large building by providing them prior information of a building layout as it is difficult to see through due to heavy smoke. This project develops an approach to show via GUI information of a region with the help of motes transferring data wirelessly. It is a 3-tier application including a server, a mobile client and a mote setup. The motes execute TinyOS, which is specifically designed operating system for sensor networks. The project has been tested in the computer science department building, Crossbow’s TelosB motes have been used for the mote setup. The programs for the motes are written in nesC (dialect of C), and the client and the server program are written in Java.
Keywords: Sensor Network; GUI; Computer Science (0984)